Formation of a multigrain structure and its influence on the strength and plasticity of the Ni3Al intermetallic compound - Ovcharenko V. E. Vladimir Efimovich; Boyangin E. N. Evgeny Nikolaevich; Myshlyaev M. M. Mikhail Mikhaylovich; Ivanov Yu. F. Yury Fedorovich; Ivanov K. V. Konstantin Veniaminovich (2015, 2015)
Title screen